Privacy and digital data of children with disabilities : scenes from social media sharenting - Goggin, Gerard (2020)
Children with disabilities have been an overlooked group in the debates on privacy and data management, and the emergence of discourses on responsibilization. In this article, we offer a preliminary overview, conceptualization, and reflection on children with disabilities, their experiences and perspectives in relation to privacy and data when it comes to existing and emergent digital technology. To give a sense of the issues at play, we provide a brief case study of “sharenting” on social media platform (that is, sharing by parents of images and information about their children with disabilities). We conclude with suggestions for the research and policy agenda in this important yet neglected area.